Note from the Editor-in-Chief - Subramanyan, Vighnesh (Consilience, 2011)
Dear readers, It is my privilege to present you Issue 6 of Consilience. Our editorial board has been working tirelessly through the late spring and summer to put this issue together, which at 319 pages is by far our longest and most ambitious issue. It is also a very international issue, as we published submissions from five continents, from Norway to Uganda, on topics as diverse as fisheries management, malarial vaccination resistance and the validity of economic measures. Impressive statistics aside, we are proud to remain a student-run journal that showcases work by a range of authors, including undergraduate and graduate students, scholars and members of the broader sustainable development community, on a wide array of topics. I would like to take this opportunity to offer a few thanks: to our absolutely fantastic editorial team, whose intelligence and dedication continue to inspire me; to our outgoing Editor-in-Chief and Managing Editor, Monica Varman and Delphia Polle, for their tireless dedication toConsilience; to our incoming leadership team, Felipe Goncalves, Jodie Liu and Kelsey Umemoto, for their constant effort on this issue. I offer a large thanks to our authors, whose effort is the substance of this journal. And, finally, to you, our readers, who have helped spread word of Consilience to far-flung corners of the world. Our presence as a leading, student-driven voice on the global stage is very much due to you. As we continue to expand the range of media which we use to publish interdisciplinary research at the cutting edge of the field, I encourage you to continue engaging with us. Enjoy the issue! Vighnesh Subramanyan Editor-in-Chief Consilience: The Journal of Sustainable Development August 30, 2011